An Overview Of Healthy House And Incidence Of Pulmonary Tuberculosis Disease - Eppy Setiyowati; Nunik Purwanti; Umi Hanik (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Some members of the public still do not understand healthy homes, this causes one family member to have pulmonary tuberculosis. The purpose of this study was to analyze the relationship of healthy home knowledge level with the incidence of pulmonary tuberculosis disease in Surabaya. Design analytical research across sectional. A research image of 70 people, A large sample of 60 respondents was taken with the Simple Random Sampling technique. Independent variable levels of healthy home knowledge and variable dependent incidence of pulmonary TB disease. The data were analyzed using the statistic test Chi-Square with a p-value ≤ of 0.05. The results of the study were obtained from 60 respondents, with almost some (38.3%) low level of knowledge about healthy homes and most (68.3%) people with pulmonary TB. Data analyzed with Chi-Square statistic tests showed p=0.03 p-value ≤0.05, which means there is a relationship between healthy home knowledge levels and pulmonary TB disease. The conclusion of a healthy home does not cause the outbreak of pulmonary tuberculosis.